Karakteristik dan Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Pembelian Buah Jeruk Lokal dan Impor di Denpasar Bali - Nyoman Utari Vipriyanti; I Ketut Arnawa; Anita Anul (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Recently, imported oranges have dominated Bali's local market, leading to low demand for local oranges because both oranges have different tastes, colors, and sizes. Research about the demand rate of local oranges in traditional markets is abundant. However, analysis that compares local and imported oranges' characteristics and supermarket consumer preferences is still lacking. This study aimed to determine (1) consumer preferences for the attributes of local and imported oranges in supermarkets in Denpasar City and (2) Factors that affected consumer decisions in buying local and imported oranges. The location of this study was determined purposively at four modern markets in Denpasar City with 100 respondents. The results showed that (1) Most consumers of oranges (68 percent) in the contemporary market are women, with 79 percent preferring to buy local oranges and only 21 percent preferring to buy imported oranges. In contrast, male consumers prefer imported oranges (69 percent), and only 31 percent prefer local oranges. This illustrates that female consumers tend to buy household needs and play a more significant role in making purchasing decisions for daily needs, including the demand for fruit. Consumers who bought oranges fruits were dominated by women, with a majority of the productive age range between 20 and 30 years (38%). Cumulative preference showed that local oranges were in the strongly like category. At the same time, imported oranges were in the neutral type only. (2) The attributes of local orange and imported oranges, such as taste, color, and texture, significantly influence consumer decisions in buying local and imported oranges. This study only emphasizes five attributes of orange without considering household income, ethnicity, and culture inside the model.